2018
DOI: 10.1155/2018/1789892
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ovine Whey Powders on Durum Wheat-Based Doughs

Abstract: Two types of ovine whey powder, with different protein content, were added at increasing substitution rates to two types of semolina, one with strong and tenacious gluten and the other with weak and sticky gluten. For each dough the optimum mixing time and hydration level were calculated using the consistograph. The whey powder negatively affected the leavening volume of all doughs, at all percentages except the lowest one (5%), mainly because of its effects on the elastic component of gluten as measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Flour quality was tested according to the International and Romanian standards: moisture (ICC 110/1), ash (ICC 104/1), wet gluten (ICC106/1), gluten deformation index (SR 90:2007) and falling number (ICC 107/1) were evaluated. The water absorption capacity (at 15% moisture basis) of wheat flour was determined by using a Consistograph (Chopin Technologies, France), according to the method described by Secchi et al [ 33 ], following the AACC approved method 54-50. The evaluation of wheat dough empirical rheological characteristics in terms of dough tenacity—maximum pressure ( P ) representing the peak height (mm), dough extensibility ( L ) indicated by the length (mm) of the alveogram curve, baking strength ( W ), swelling index ( G ) and configuration ratio of the curve ( P/L ) were achieved using the Alveograph instrument (Chopin Technologies, France), according to the SR EN ISO 27971:2015 standard.…”
Section: Methodsmentioning
confidence: 99%
“…Flour quality was tested according to the International and Romanian standards: moisture (ICC 110/1), ash (ICC 104/1), wet gluten (ICC106/1), gluten deformation index (SR 90:2007) and falling number (ICC 107/1) were evaluated. The water absorption capacity (at 15% moisture basis) of wheat flour was determined by using a Consistograph (Chopin Technologies, France), according to the method described by Secchi et al [ 33 ], following the AACC approved method 54-50. The evaluation of wheat dough empirical rheological characteristics in terms of dough tenacity—maximum pressure ( P ) representing the peak height (mm), dough extensibility ( L ) indicated by the length (mm) of the alveogram curve, baking strength ( W ), swelling index ( G ) and configuration ratio of the curve ( P/L ) were achieved using the Alveograph instrument (Chopin Technologies, France), according to the SR EN ISO 27971:2015 standard.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in 4T and 48T bread volume development may be due to the different rheological properties of the dough, which are determined, in turn, by the technological characteristics of the 2 types of semolina used. Secchi et al [8] reported that the dough becomes firmer, stiffer, and more elastic and solid as a consequence of the OWP supplementation, thus leading to a detrimental effect on the leavening process. This could be due to its excessive strengthening effect on the gluten matrix, which showed great resistance to the extension during fermentation, as also reported elsewhere [13].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 kg of dough for each sample was prepared in a fork mixer. The water content of dough was calculated on the basis of consistographic HYDHA values, as previously reported by Secchi et al [8], and salt percentage was 2.5% of water content [7]. The amount of baker's yeast consisted of 1.0% of the total weight of semolina plus OWP.…”
Section: Bread-making Processmentioning
confidence: 99%